Two cases reports: Severe liver injury caused by 1,2,3-trichloropropane poisoning - Li, Chen; Hu, Jinhua; Su, Haibin (Frontiers in Public Health, 2023)
Background 1,2,3-trichloropropane (TCP) poisoning can induce liver damage in humans and animals, but reports of severe liver injury and its histology are rare. We presented two cases of 1,2,3-TCP inhalation poisoning resulting in severe liver injury confirmed by exposure history, toxicology, biochemical index and pathology. Case description Two young male presented acute poisoning process with mild to moderate early symptoms, and developed severe jaundice and coagulation dysfunction after exposure to 1,2,3-TCP. The total bilirubin (TBIL) in case 1 and case 2 reached the peak value of 635.8 μmol/L and 437.1 μmol/L on the 25th and 22nd days, respectively. Their liver enzymes and international normalized ratio increased rapidly to peak and fell back, and TBIL remained at a high level. 1,2,3-TCP was detected in their blood, and their liver histology indicated severe necrosis of hepatocytes, infiltration of massive inflammatory cells, and cholestasis. They all finally recovered after a long time of treatment. Conclusion The two cases in this study demonstrate that 1,2,3-TCP inhalation poisoning without any protective measures can induce severe liver injury in humans.